Ultraviolet-curable liquid natural rubber - Pranee Phinyocheep (2018)
Preparation of ultraviolet (UV)-curable liquid natural rubber was achieved by fixation of photosensitive molecule onto liquid natural rubber. The liquid natural rubber (LNR) was prepared by oxidative degradation of natural rubber latex, using the phenylhydrazine/O2 system. The LNR was further treated with in situ performic acid, which leads to epoxidized liquid natural rubber (ELNR). The progress of the addition reaction of photosensitive acrylic acid onto epoxide ring of the ELNR was followed by infrared spectroscopy. It was found that at 80 °C reaction temperature, epoxide ring opening reaction of ELNR came to completion within 2 h, which is faster than the reaction at 60 °C. The photocrosslinking reaction of the acrylated ELNR was studied by monitoring the exothermic heat of photocuring of acrylate double bond using a double beam photocalorimeter (DPA7). It was found that the fast crosslinking-polymerization occurred when the rubber was exposed to UV irradiation in the presence of photocleavage initiator (Irgacure 184 and Darocur 1173) and liquid diacrylate monomer (1,6 hexanediol diacrylate and tripropylene glycol diacrylate). The cure kinetics of the elastomers were also investigated, and it was found that the diacrylate monomer, photoinitiator concentration play an important role on the rate and extent of the reaction.